The Challenge of Sustainable Land-Based Local Economic Development in Poor Communities of South Africa: The Case of Groblershoop, Northern Cape - Parker, Gail, Denise (My University, 2021)
Since the advent of South Africa’s democracy, there have been many pressing questions; one of which has been: ‘to what extent has the newly found political and civil freedoms, which is guaranteed for all South Africans, translated into an a more economically-viable life?’ This research investigates whether local economic development (LED) interventions necessarily improve the livelihoods of poor communities. More specifically, the goal of this thesis is to explore some of the reasons why land-based economic development interventions often struggle to meet their main objective of improving the livelihoods of local poor people. It is hoped that the findings of this research will assist policymakers and local economic development planners in making more informed decisions. Using a qualitative research methodology, a three- pronged approach is adopted to address the key goal of this thesis. First, a review of the literature on LED was conducted: a comparative study into its origins in wealthy, developed countries; and the experiences on the successes and failures of LED as a developmental tool. Secondly, a review was made of the experiences of the application on LED approaches in a South African context, with special reference to the policy and support of LED strategy. Thirdly, a case study of Groblershoop, which is in the Northern Cape, is presented. It focuses on LED that is based on land, and the role that it plays in the livelihood approaches of poor people. In conclusion, it is posited that while the potential of land-based LED is not disputed, the implementation of such strategies are often inconsistent with the overall objective of poverty alleviation and economic development. For this reason, local municipalities will not be able to do this without clear policy guidance; institutional capacity-building; inter-sectoral collaboration of political ‘champions’ to drive the process; and real empowerment of the beneficiaries whom the projects are supposed to assist.
Keywords: Local Economic Development; South Africa; land